A review of prevention, diagnosis, and treatment of Relative Energy Deficiency in sport in artistic (synchronized) swimming - Robertson, S.; Mountjoy, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
The syndrome of relative energy deficiency in sport (RED-S) is a clinical entity characterized by low energy availability, which can negatively affect the health and performance of both male and female athletes. The underlying mechanism of RED-S is an inadequacy of dietary energy to support optimal health and performance. This syndrome refers to impaired physiological function, including metabolic rate, menstrual function, bone health, immunity, protein synthesis, and cardiovascular health, with psychological consequences that can either precede (through restrictive dietary habits) or result from RED-S. The term RED-S extends beyond the condition termed the "Female Athlete Triad." Formerly known as synchronized swimming, artistic swimming is an Olympic sport requiring a high level of fitness as well as technical skill and artistry. The risk of RED-S is high in artistic swimming as it is an aesthetic, judged sport with an emphasis on a lean physique. RED-S is of significant concern in the sport of artistic swimming because of the potential negative effects on physical and mental health as well as consequences on athletic performance. This paper reviews health and performance consequences associated with low energy availability resulting in RED-S in artistic swimming. Medical and nutritional considerations specific to artistic swimming are reviewed, and methods to help detect and manage RED-S are discussed. Prevention and management of RED-S in this athlete population should be a priority for coaches, and the sport medicine professionals working with artistic swimming athletes should utilize the RED-S CAT, a Clinical Assessment Tool for screening and managing RED-S.